A comparison between Qigong exercise and cycle ergometer exercise for the rehabilitation of chronic obstructive pulmonary disease: A pilot randomized controlled trial (CONSORT). Issue 21 (28th May 2021) - Dong, Xiaosheng; Wang, Xiangyu; Jia, Ningxin; Chen, Xianhai; Ding, Meng
Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a common respiratory disease that is associated with significant morbidity and mortality. Exercise training confers health benefits to people with COPD. The purpose of this study was to compare differences in the rehabilitation of COPD between Qigong exercise (QE) and aerobic exercise using a cycle ergometer (CE). Methods: This study was a randomized single-blind controlled trial. Twenty six participants were recruited and randomized to either the Qigong group or the cycle ergometer group. Both interventions lasted 12 weeks and comprised a 30 minutes supervised training session performed twice a week, that is, 24 sessions in total. The primary outcome measure was the endurance capacity measured by the six-minute walk test (6MWT). The secondary outcome measures were the results of the St. George's Hospital Respiratory Questionnaire (SGRQ) and the COPD assessment test (CAT). Results: Participants in the group that performed aerobic exercise using a cycle ergometer had significantly improved 6MWT ( P  = .005), SGRQ ( P  = .029), and CAT ( P  = .018) results. Participants in the Qigong exercise group had significant changes in 6MWT ( P  = .033). However, the differences in 6MWT and SGRQ were not statistically significant between the 2 groups. The changes in CAT scores before and after the intervention were significantly different between the 2 groups ( P  = .020). There were no reports of adverse events during the course of the trial. Conclusions: There was no difference in the primary outcome between groups. In particular, QE and cycle ergometer exercise had similar rehabilitation effects on the improvement of the cardiopulmonary endurance and quality of life of chronic obstructive pulmonary disease patients. In addition, cycle ergometer exercise may lead to a better trend of improvement in the quality of life and can improve the severity of the clinical symptoms of chronic obstructive pulmonary disease. Trial registration: ChiCTR-TRC-14004404.